2007
DOI: 10.1016/j.acra.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Search in Multitrauma Patients: Severity of Detected Fractures

Abstract: Purpose-Satisfaction of search (SOS) occurs when an abnormality is missed because another abnormality has been detected. This research studied whether the severity of a detected fracture determines whether subsequent fractures are overlooked.Materials and Methods-Each of seventy simulated multi-trauma patients presented examinations of three anatomic areas. Readers evaluated each patient under two experimental conditions: when the images of the first anatomic area included a fracture (the SOS condition), and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Additionally, double reading strategies of CT and X-ray images have been proven to reduce the incidence of missed injuries [1]. Berbaum et al [3] analysed the 'satisfaction of search' effect, i.e. the effect that concomitant injuries are missed after one, often serious, injury has been detected, in diagnostic imaging by systematically adding fractures of different severity to the image collection of multiple trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, double reading strategies of CT and X-ray images have been proven to reduce the incidence of missed injuries [1]. Berbaum et al [3] analysed the 'satisfaction of search' effect, i.e. the effect that concomitant injuries are missed after one, often serious, injury has been detected, in diagnostic imaging by systematically adding fractures of different severity to the image collection of multiple trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the severity of the patient's presentation is inversely related to the detection of secondary trauma (5). This is partly due to the 'satisfaction of search', which is the propensity to overlook less obvious conditions after detecting a more apparent injury (13,14). In addition, because a large number of patients with scapular fractures are unconscious at the time of presentation, a brachial plexus examination must wait and, thus, can be forgotten later in a patient's hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…1.1 Perception research with actual medical images is difficult because of the lack of control of the images and because of the lack of truth data [1][2][3][4][5]. We have developed software tools that allow the manipulation of images to remove or introduce abnormalities specifically for perception research [6].…”
Section: Introductionmentioning
confidence: 99%